Features of the translation of elliptical utterances in the spoken Japanese language - К.Е., Муратова; Е.А., Ахaпов (Journal of Oriental Studies, 2020)
This work is devoted to the study of the translation of elliptical constructions in oral speech. The characterization of ellipsis in Japanese and creation its typology. Ellipsis as a phenomenon is a basic characteristic of every language. It is commonly found in several languages, one of which is Japanese. Ellipsis causes difficulties in learning the language, since problems might arise not with unfamiliar vocabulary presented in the text, but on the contrary with words missing in it. In addition, ellipsis is considered an important element in the culture of interpersonal communication between Japanese people, when in a speech both individual words and significant parts of the utterance can be omitted, and the listener should be able to independently recover the missing information based on the context, specific speech situation or his background knowledge. The problems of perception and translation of elliptical structures can be solved by forming a conscious idea of the ellipsis and the rules of its functioning in Japanese. This skill is one of the most important in the perception of oral and written speech in natural conditions, and the ability to independently use elliptical constructions makes speech less complicated, which allows it to sound more natural. Key words: ellipsis, elliptical constructions, linguistics, translation, oral speech.